A Fuzzy Risk Assessment Model for Hospital Information System Implementation - Özok, Ahmet Fahri; Yücel, Gülçin; Hoege, B.; Çebi, Selçuk (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2012)
There is research which reveals negative effects of IT applications in the healthcare sector on both patients and staff. Therefore, methods are necessary to predict the risk of new healthcare information technology in order to reduce the unintended results of new applications. A new predictive risk assessment model for a hospital information system (HIS) has been developed in this paper to estimate risk before the implementation of new HIS. The methodology consists of analytic network process (ANP), reality-design gap evaluation and fuzzy inference system. An application of the proposed algorithm has been applied for a research and education hospital in Istanbul, Turkey. Risk magnitude of a new HIS implementation for the hospital is found as major with a belief of 100%. The relative importances of risk factors for HIS implementation success are obtained. The most effective factors on the HIS implementation are found as technological factors; usefulness, compatibility, user involvement and ease of use. These factors are followed by organizational factors; training and organizational commitment. The most important individual factor is also found as user's previous HIS experience. A risk assessment model has been proposed in this paper. The model processes experts' evaluations defined in linguistic forms when there is no sufficient data and it integrates possible risk factors into the decision-making process of risk assessment. In the model, a reality-design gap analysis is used to determine risk likelihood instead of directly risk evaluation. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: hospital information system; risk assessment; analytic network process; fuzzy inference system; decision making; hastane bilgi sistemi; risk değerlendirmesi; analitik ağ süreci; bulanık çıkarım sistemi; karar verme